Non-asphalt-based anti-aging waterproof coiled material and preparation method thereof

Through the use of non -aslerate -based materials and multi -layer composite structure design, the aging problem of asphalt waterproof coils is solved, and the improvement of aging, wear resistance and waterproof performance is suitable for multiple building environments.

CN119348263AActive Publication Date: 2025-01-24DAYU JIUDING NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411554650.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing asphalt waterproof coils have degraded performance and waterproof failure due to the aging problem of modified asphalt.

Method used

Non-aslerate-based materials, including main layers, surface aging layers, adhesive layers, and abrasion-resistant enhanced layers. Performance additives and surface modification techniques for nanomaterials are prepared to prepare composite materials with aging resistance, wear resistance and waterproof performance.

Benefits of technology

The significant improvement of the aging resistance, abrasion resistance and waterproof performance of non -aslerate waterproof coils, extended the service life, improved the mechanical strength and waterproof effect, and was suitable for various architectural environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a non-asphalt-based anti-aging waterproof coiled material and a preparation method thereof. A main body layer is prepared from thermoplastic polyolefin resin, an ethylene-vinyl acetate copolymer and fiber filler; the surface anti-aging layer is composed of nano titanium dioxide, 2-(2 '-hydroxy-5'-methylphenyl) benzotriazole, a hindered phenol antioxidant, a phosphite ester auxiliary antioxidant, an organic tin stabilizer, a rare earth stabilizer, a silane coupling agent and a nonionic surfactant; the wear-resistant reinforcing layer is prepared from a methyl methacrylate-butadiene-styrene copolymer, nano aluminum oxide, gamma-methacryloxy propyl trimethoxy silane, epoxy resin, an initiator and an accelerant. The invention relates to the technical field of waterproof coiled materials. A methyl methacrylate-butadiene-styrene copolymer is used as a matrix, nano aluminum oxide is added as a wear-resistant filler, and surface modification treatment is performed to prepare the material with excellent wear resistance and comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof coiled materials, and in particular to a non-asphalt-based aging-resistant waterproof coiled material and a preparation method thereof. Background Art

[0002] Asphalt waterproofing membrane is the most important material in the field of building waterproofing applications. It is mainly made of base paper, fiber felt and other base materials dipped in asphalt, and the surface is sprinkled with powdered, granular or flaky materials to make a rollable sheet waterproof material. Among asphalt waterproofing membranes, those made of thick paper or glass cloth and other base materials dipped in petroleum asphalt are called base membranes; and those made by mixing asbestos, rubber powder, etc. into asphalt materials and rolling them are called roll-pressed membranes, that is, baseless membranes. Since modified asphalt is directly exposed to the atmosphere, it will age severely, causing the performance of the modified asphalt to decline and leading to waterproof failure. Therefore, all exposed asphalt waterproofing membranes will be covered with anti-aging isolation materials on the asphalt surface to form a protective layer to prevent the membrane from long-term direct ultraviolet rays and isolate most of the oxygen, thereby reducing the impact of aging factors such as ultraviolet rays and oxygen. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a non-asphalt-based aging-resistant waterproofing coiled material, which consists of a main body layer, a surface aging-resistant layer, a bonding layer and a wear-resistant reinforcement layer; The main body layer is composed of thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer and fiber filler; The surface anti-aging layer is composed of nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant; The bonding layer is composed of terpene resin and butyl rubber; The wear-resistant reinforcement layer is composed of methyl methacrylate-butadiene-styrene copolymer, nano-aluminum oxide, gamma-methacryloxypropyltrimethoxysilane, epoxy resin, initiator and accelerator.

[0004] Preferably, a non-asphalt-based aging-resistant waterproofing membrane comprises the following components by weight: 40-45 parts by weight of thermoplastic polyolefin resin, 25-30 parts by weight of ethylene-vinyl acetate copolymer, 10-12 parts by weight of fiber filler, 10-15 parts by weight of nano titanium dioxide, 5-10 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 3-5 parts by weight of hindered phenol antioxidant, 2-4 parts by weight of phosphite auxiliary antioxidant, 3-6 parts by weight of organic tin stabilizer, and 10-15 parts by weight of nano titanium dioxide. 2-5 parts by weight of soil stabilizer, 1-3 parts by weight of silane coupling agent, 1-2 parts by weight of nonionic surfactant, 3-5 parts by weight of terpene resin, 2-4 parts by weight of butyl rubber, 40-50 parts by weight of methyl methacrylate-butadiene-styrene copolymer, 10-16 parts by weight of nano alumina, 3-6 parts by weight of γ-methacryloxypropyltrimethoxysilane, 20-30 parts by weight of epoxy resin, 0.5-1.5 parts by weight of initiator and 0.1-0.4 parts by weight of accelerator.

[0005] Preferably, the fiber filler is composed of carbon fiber and polyester fiber, the hindered phenol antioxidant is 2,6-di-tert-butyl-4-methylphenol, the phosphate auxiliary antioxidant is triester phosphite, the non-ionic surfactant is fatty alcohol polyoxyethylene ether, the initiator is dibenzoyl peroxide, and the accelerator is dimethylaniline.

[0006] A method for preparing a non-asphalt-based aging-resistant waterproof coiled material comprises the following steps: Step 1: Purchase and inspect raw materials. Purchase thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer, fiber filler, nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent, non-ionic surfactant, terpene resin, butyl rubber, methyl methacrylate-butadiene-styrene copolymer, nano alumina, γ-methacryloxypropyltrimethoxysilane, epoxy resin, initiator and accelerator according to the formula requirements; Step 2: Preparation of the main body layer: adding thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer and fiber filler into a high-speed mixer, mixing for 15-20 minutes at a temperature of 80-100°C and a rotation speed of 1000-1500r / min, adding the mixed materials into a special extruder for the main body layer, heating and plasticizing in the extruder, extruding through a die to form a main body layer sheet, and then cooling and shaping; Step 3: Preparation of the surface anti-aging layer, adding nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant into another high-speed mixer, mixing at a temperature of 60-80°C for 10-15 minutes, adding the mixed materials into a special extruder for the anti-aging layer, extruding to form an anti-aging layer sheet, and then drying; Step 4: Preparation of the bonding layer: Add the terpene resin and butyl rubber into a small mixer and mix at room temperature for 5-10 minutes; Step 5: Preparation of wear-resistant reinforcement layer: Add nano-alumina to an appropriate amount of ethanol, perform ultrasonic dispersion, slowly drop γ-methacryloxypropyltrimethoxysilane into the above dispersion, stir continuously during the dropwise addition, continue stirring after the dropwise addition is completed, reflux the mixed solution for reaction, and after the reaction is completed, obtain surface-modified nano-alumina by centrifugal separation, wash with ethanol 3-5 times to remove unreacted γ-methacryloxypropyltrimethoxysilane and impurities, and then vacuum dry for use; Prepolymerization reaction: add methyl methacrylate-butadiene-styrene copolymer into a reactor, heat until completely melted, add epoxy resin into the reactor, stir evenly, then add initiator, continue stirring and heating to carry out prepolymerization reaction; Blending reaction: adding the surface-modified nano-alumina to the above-mentioned prepolymer, adding a promoter at the same time, mixing the mixture thoroughly and evenly under high-speed stirring, then heating up to continue the reaction, and after the reaction is completed, naturally cooling to room temperature to obtain a wear-resistant reinforcement layer; Adding the prepared wear-resistant reinforcement layer into a special extruder for the wear-resistant reinforcement layer, and extruding to form a wear-resistant reinforcement layer sheet; Step 6: Compounding the coiled material: Compounding the prepared main layer, surface anti-aging layer, bonding layer and wear-resistant reinforcement layer through a laminating device in the order of main layer-bonding layer-wear-resistant reinforcement layer-bonding layer-surface anti-aging layer, and further calendering the compounded coiled material through a calendering machine; Step seven: Post-processing, cooling the composite waterproof membrane.

[0007] Preferably, the ultrasonic dispersion time in step 5 is 30-60 minutes, and the stirring time after the dropwise addition is set to 2-3 hours; The reflux reaction temperature of the mixed solution is set to 60-80°C, and the reflux reaction time is set to 4-6 hours; The vacuum drying temperature is set to 80-100°C, and the vacuum drying time is set to 6-8 hours.

[0008] Preferably, in the prepolymerization reaction, the heating temperature is set to 80-100° C., the heating temperature is set to 120-130° C., and the prepolymerization reaction time is set to 1-2 hours.

[0009] Preferably, the heating temperature in the blending reaction is set to 140-150° C., and the reaction time is set to 2-3 hours.

[0010] Preferably, the preparation method of 2,6-di-tert-butyl-4-methylphenol is as follows: p-cresol is added to a reaction kettle, and then concentrated sulfuric acid is slowly added as a catalyst, and the catalyst is stirred while being added to uniformly disperse the catalyst. Afterwards, isobutylene gas is slowly introduced under certain temperature and pressure conditions. The reaction temperature is generally controlled at 50-70°C, the pressure is maintained at 0.2-0.5MPa, and the reaction time is 4-6 hours. After the reaction is completed, sodium hydroxide solution is used for neutralization to make the pH value of the reaction system reach a neutral value. After neutralization, water washing is performed to remove water-soluble impurities such as salts generated during the reaction. Water washing generally needs to be repeated multiple times until the pH value of the washing liquid remains substantially unchanged. 2,6-di-tert-butyl-4-methylphenol is separated and purified by a reduced pressure distillation method to obtain 2.

[0011] Preferably, the preparation method of the triester phosphite is to add the solvent toluene into a reaction kettle, then slowly add 2,4-di-tert-butylphenol and stir to dissolve it, then slowly drop phosphorus trichloride at a low temperature of 0-10°C, strictly control the temperature during the dropwise addition, and after the dropwise addition is completed, slowly heat up to the reflux temperature, the reflux temperature is about 110-112°C, react for 3-5 hours, neutralize and wash with water after the reaction, and then separate and purify by a reduced pressure distillation method to obtain the triester phosphite.

[0012] Preferably, the preparation method of the fatty alcohol polyoxyethylene ether comprises adding a fatty alcohol and an alkaline catalyst into a reactor, closing the reactor and evacuating the reactor to remove air and moisture in the reaction system, then slowly introducing ethylene oxide at a temperature of 120-180°C and a pressure of 0.2-0.5MPa to react, neutralizing and washing after the reaction, and then separating and purifying by a reduced pressure distillation method to obtain the fatty alcohol polyoxyethylene ether.

[0013] The present invention provides a non-asphalt-based aging-resistant waterproof coiled material and a preparation method thereof, and the beneficial effects thereof are: 1. Material innovation: A new type of modified polymer material is used in the wear-resistant reinforcement layer. With methyl methacrylate-butadiene-styrene copolymer as the matrix, nano-alumina is added as a wear-resistant filler, and the surface is modified. At the same time, it is combined with epoxy resin and other ingredients to prepare a material with excellent wear resistance and comprehensive performance. The application of this new material is innovative in the field of non-asphalt-based waterproof membranes, breaking through the performance limitations of traditional materials, improving the surface wear resistance of the membrane, and providing the possibility for the application of waterproof membranes in some special environments.

[0014] 2. The coordinated use of multiple high-performance additives. A variety of high-performance additives are used in the formula, such as nano titanium dioxide, benzotriazole ultraviolet absorbers, hindered phenol antioxidants, phosphite auxiliary antioxidants, organic tin stabilizers, rare earth stabilizers, etc. These additives improve the performance of the membrane from different aspects. Their synergistic effect makes the waterproof membrane have significant advantages in aging resistance, oxidation resistance, stability, etc. This design concept of the coordinated use of multiple additives is innovative in the formulation of waterproof membranes and provides new ideas and methods for improving product performance.

[0015] 3. Surface modification and dispersion process of nanomaterials. According to the characteristics of nano titanium dioxide and nano aluminum oxide, a specific surface modification process and dispersion method are adopted. Through ultrasonic dispersion and surface modification with silane coupling agent (such as KH570), the problem of easy agglomeration of nanomaterials in polymer matrix is ​​effectively solved, and its dispersion uniformity and compatibility with the matrix are improved. This nanomaterial processing technology is innovative in the production of waterproof membranes, providing technical guarantee for giving full play to the excellent performance of nanomaterials, and also providing reference for nano applications in other related material fields.

[0016] 4. Preparation process of multi-layer composite structure. This scheme adopts a unique multi-layer composite structure preparation process, which reasonably combines and compounds the main layer, surface anti-aging layer, bonding layer and wear-resistant reinforcement layer. By precisely controlling the preparation process parameters of each layer and the pressure, temperature and other conditions of the interlayer composite, the close combination and synergy between the layers are achieved, so that the waterproof membrane has a variety of excellent properties. The design and preparation process of this multi-layer composite structure are innovative in the field of non-asphalt-based waterproof membranes, breaking through the limitations of traditional single-layer or simple multi-layer structures, and opening up a new way to improve the comprehensive performance of waterproof membranes.

[0017] 5. Significant improvement in comprehensive performance. Through the innovation of materials and processes, the non-asphalt-based aging-resistant waterproof membrane prepared by this scheme has been significantly improved in terms of aging resistance, wear resistance, waterproof performance and mechanical strength. Compared with traditional waterproof membranes, it has a longer service life, better wear resistance and more reliable waterproof effect, and can meet the needs of some special construction projects with high requirements for waterproof membrane performance. This innovative improvement in comprehensive performance provides a better solution for the field of building waterproofing and promotes the development and progress of waterproof membrane technology.

[0018] 6. Multifunctionality: This waterproof membrane not only has basic waterproofing function, but also integrates multiple functions such as aging resistance and wear resistance by adding different functional layers and materials. This multifunctional design concept conforms to the development trend of modern building materials, provides users with a multifunctional integrated product, reduces the use and matching of multiple functional materials during construction, improves construction efficiency and project quality, and has strong market competitiveness and application prospects. DETAILED DESCRIPTION

[0019] The following embodiments further describe the present invention in detail. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and design various embodiments with various modifications suitable for specific uses.

[0020] Embodiment 1, a non-asphalt-based aging-resistant waterproofing membrane, the membrane comprising a main body layer, a surface aging-resistant layer, a bonding layer and a wear-resistant reinforcement layer; The main body layer is composed of thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer and fiber filler; The surface anti-aging layer is composed of nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant; The bonding layer is composed of terpene resin and butyl rubber; The wear-resistant reinforcement layer is composed of methyl methacrylate-butadiene-styrene copolymer, nano-aluminum oxide, gamma-methacryloxypropyltrimethoxysilane, epoxy resin, initiator and accelerator.

[0021] A non-asphalt-based aging-resistant waterproof coiled material comprises the following components by weight: 40 parts by weight of thermoplastic polyolefin resin, 25 parts by weight of ethylene-vinyl acetate copolymer, 10 parts by weight of fiber filler, 10 parts by weight of nano titanium dioxide, 5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 3 parts by weight of hindered phenol antioxidant, 2 parts by weight of phosphite auxiliary antioxidant, 3 parts by weight of organic tin stabilizer, 2 parts by weight of rare earth stabilizer, 1 part by weight of silane coupling agent, 1 part by weight of nonionic surfactant, 3 parts by weight of terpene resin, 2 parts by weight of butyl rubber, 40 parts by weight of methyl methacrylate-butadiene-styrene copolymer, 10 parts by weight of nano aluminum oxide, 3 parts by weight of gamma-methacryloxypropyltrimethoxysilane, 20 parts by weight of epoxy resin, 0.5 parts by weight of initiator and 0.1 parts by weight of accelerator.

[0022] The fiber filler is composed of carbon fiber and polyester fiber, the hindered phenol antioxidant is 2,6-di-tert-butyl-4-methylphenol, the phosphate auxiliary antioxidant is triester phosphite, the non-ionic surfactant is fatty alcohol polyoxyethylene ether, the initiator is dibenzoyl peroxide, and the accelerator is dimethylaniline.

[0023] Embodiment 2, a non-asphalt-based aging-resistant waterproofing membrane, the membrane comprising a main body layer, a surface aging-resistant layer, a bonding layer and a wear-resistant reinforcement layer; The main body layer is composed of thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer and fiber filler; The surface anti-aging layer is composed of nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant; The bonding layer is composed of terpene resin and butyl rubber; The wear-resistant reinforcement layer is composed of methyl methacrylate-butadiene-styrene copolymer, nano-aluminum oxide, gamma-methacryloxypropyltrimethoxysilane, epoxy resin, initiator and accelerator.

[0024] A non-asphalt-based aging-resistant waterproof coiled material comprises the following components by weight: 45 parts by weight of thermoplastic polyolefin resin, 30 parts by weight of ethylene-vinyl acetate copolymer, 12 parts by weight of fiber filler, 15 parts by weight of nano titanium dioxide, 10 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 5 parts by weight of hindered phenol antioxidant, 4 parts by weight of phosphite auxiliary antioxidant, 6 parts by weight of organic tin stabilizer, 5 parts by weight of rare earth stabilizer, 3 parts by weight of silane coupling agent, 2 parts by weight of nonionic surfactant, 5 parts by weight of terpene resin, 4 parts by weight of butyl rubber, 50 parts by weight of methyl methacrylate-butadiene-styrene copolymer, 16 parts by weight of nano aluminum oxide, 6 parts by weight of gamma-methacryloxypropyltrimethoxysilane, 30 parts by weight of epoxy resin, 1.5 parts by weight of initiator and 0.4 parts by weight of accelerator.

[0025] The fiber filler is composed of carbon fiber and polyester fiber, the hindered phenol antioxidant is 2,6-di-tert-butyl-4-methylphenol, the phosphate auxiliary antioxidant is triester phosphite, the non-ionic surfactant is fatty alcohol polyoxyethylene ether, the initiator is dibenzoyl peroxide, and the accelerator is dimethylaniline.

[0026] Embodiment 3, a non-asphalt-based aging-resistant waterproofing membrane, the membrane comprising a main body layer, a surface aging-resistant layer, a bonding layer and a wear-resistant reinforcement layer; The main body layer is composed of thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer and fiber filler; The surface anti-aging layer is composed of nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant; The bonding layer is composed of terpene resin and butyl rubber; The wear-resistant reinforcement layer is composed of methyl methacrylate-butadiene-styrene copolymer, nano-aluminum oxide, gamma-methacryloxypropyltrimethoxysilane, epoxy resin, initiator and accelerator.

[0027] A non-asphalt-based aging-resistant waterproof coiled material comprises the following components by weight: 42.5 parts by weight of thermoplastic polyolefin resin, 27.5 parts by weight of ethylene-vinyl acetate copolymer, 11 parts by weight of fiber filler, 12.5 parts by weight of nano titanium dioxide, 7.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 4 parts by weight of hindered phenol antioxidant, 3 parts by weight of phosphite auxiliary antioxidant, 4.5 parts by weight of organic tin stabilizer, 3.5 parts by weight of rare earth stabilizer, 2 parts by weight of silane coupling agent, 1.5 parts by weight of nonionic surfactant, 4 parts by weight of terpene resin, 3 parts by weight of butyl rubber, 45 parts by weight of methyl methacrylate-butadiene-styrene copolymer, 13 parts by weight of nano aluminum oxide, 4.5 parts by weight of gamma-methacryloxypropyltrimethoxysilane, 25 parts by weight of epoxy resin, 1 part by weight of initiator and 0.25 parts by weight of accelerator.

[0028] The fiber filler is composed of carbon fiber and polyester fiber, the hindered phenol antioxidant is 2,6-di-tert-butyl-4-methylphenol, the phosphate auxiliary antioxidant is triester phosphite, the non-ionic surfactant is fatty alcohol polyoxyethylene ether, the initiator is dibenzoyl peroxide, and the accelerator is dimethylaniline.

[0029] Example 4, based on Example 1, Example 2 and Example 3, a method for preparing a non-asphalt-based aging-resistant waterproof membrane comprises the following steps: 1. Preparation Raw material procurement and inspection According to the formula requirements, we purchase high-quality thermoplastic polyolefin (TPO) resin, ethylene-vinyl acetate copolymer (EVA), fiber filler, nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl) benzotriazole, hindered phenol antioxidants, phosphite auxiliary antioxidants, organic tin stabilizers, rare earth stabilizers, silane coupling agents, non-ionic surfactants, terpene resins, butyl rubber, methyl methacrylate-butadiene-styrene copolymer (MBS), nano alumina, γ-methacryloxypropyltrimethoxysilane (KH570), epoxy resin (E-44), initiator (dibenzoyl peroxide, BPO) and accelerator (dimethylaniline, DMA).

[0030] Inspect the purchased raw materials to ensure that their quality meets the relevant standards and formula requirements, such as checking the molecular weight and purity of the resin, the active ingredient content of the additives, etc.

[0031] Equipment debugging Prepare high-speed mixers, extruders (different screw structures and specifications for each layer), calenders, laminating equipment, drying equipment, winding equipment, etc.

[0032] Debug the equipment's temperature control system, pressure control system, speed control system, etc. to ensure that the equipment can operate stably during production and meet the required process parameter requirements. For example, the screw temperature of the extruder should be set according to the characteristics of the raw materials in different layers, and the temperature generally increases gradually from the feeding section to the die head.

[0033] 2. Preparation of each layer Main layer preparation Thermoplastic polyolefin (TPO) resin, ethylene vinyl acetate copolymer (EVA) and fiber filler are added to a high-speed mixer.

[0034] Mix for 15-20 minutes at a certain temperature (80-100℃) and speed (1000-1500r / min) to ensure that the raw materials are fully mixed.

[0035] Add the mixed materials into the special extruder for the main layer. The screw speed of the extruder is adjusted to 30-50r / min according to the production speed requirements, and the body temperature is controlled at 180-220℃.

[0036] After the material is heated and plasticized in the extruder, it is extruded through a die to form a main layer sheet, and then cooled and shaped. Air cooling or water cooling can be used to reduce its temperature to room temperature.

[0037] Preparation of surface aging-resistant layer Add nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant into another high-speed mixer.

[0038] Mix at a relatively low temperature (60-80°C) for 10-15 minutes to avoid excessive temperature which may cause decomposition or ineffectiveness of certain additives.

[0039] Add the mixed materials into the special extruder for the anti-aging layer. The temperature of the extruder is controlled at 160-190℃ and the screw speed is 20-40r / min.

[0040] The aging-resistant layer sheet is formed by extrusion, and the thickness is controlled according to the design requirements. After extrusion, it can be slightly stretched to orient its molecular chains and improve its performance. It is then dried to remove moisture and volatile components. The drying temperature is 80-100°C and the time is 2-3 hours.

[0041] Adhesive layer preparation Add terpene resin and butyl rubber into a small mixer and mix at room temperature for 5-10 minutes to make them evenly mixed.

[0042] The mixed adhesive is evenly coated on one side of the main layer or the wear-resistant reinforcement layer through a coating device. The coating thickness is 0.1-0.3mm, which can be adjusted according to the bonding performance requirements.

[0043] Preparation of wear-resistant reinforcement layer (new modified polymer material) Nano-alumina surface modification: Add nano-alumina into a proper amount of ethanol and perform ultrasonic dispersion for 30-60 minutes to make it evenly dispersed in the ethanol solution.

[0044] Slowly drop KH570 into the above dispersion, the amount of KH570 is 3-6 parts by weight of nano-alumina, stir continuously during the dropwise addition, and continue stirring for 2-3 hours after the dropwise addition is completed.

[0045] Then the mixed solution is refluxed at 60-80° C. for 4-6 hours to allow KH570 to fully react with the hydroxyl groups on the surface of the nano-alumina.

[0046] After the reaction is completed, the surface-modified nano-alumina is obtained by centrifugal separation, washed with ethanol for 3-5 times to remove unreacted KH570 and impurities, and then vacuum dried at 80-100° C. for 6-8 hours for use.

[0047] Prepolymerization reaction: MBS was added into a reaction kettle equipped with a stirrer, a thermometer and a condenser, and heated to 80-100°C to completely melt it.

[0048] Add a certain amount of epoxy resin (E-44) into the reactor and stir evenly.

[0049] Then, the initiator BPO was added, stirring was continued and the temperature was raised to 120-130° C. to carry out prepolymerization reaction for 1-2 hours.

[0050] Blending reaction: The surface-modified nano-alumina is added to the above prepolymer, and the amount of the nano-alumina is 10-16 parts of the mass of MBS. At the same time, the accelerator DMA is added.

[0051] The mixture is fully mixed under high-speed stirring, and then the temperature is raised to 140-150°C and the reaction is continued for 2-3 hours to make the nano-aluminum oxide evenly dispersed in the polymer matrix and interact with the polymer to a certain extent.

[0052] After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a new modified polymer material.

[0053] Add the prepared new modified polymer material into the special extruder for wear-resistant reinforcement layer, control the extruder temperature at 170-200℃, and the screw speed at 25-45r / min. Extrude to form wear-resistant reinforcement layer sheet, the thickness of which is controlled according to design requirements.

[0054] 3. Coil Lamination The prepared main layer, surface anti-aging layer, bonding layer and wear-resistant reinforcement layer are compounded by bonding equipment in the order from bottom to top (main layer-bonding layer-wear-resistant reinforcement layer-bonding layer-surface anti-aging layer).

[0055] During the lamination process, appropriate pressure and temperature should be applied to ensure that the layers can be tightly bonded. The pressure is generally controlled at 0.2-0.5MPa, and the temperature is set according to the characteristics of the bonding layer, generally at 100-130℃.

[0056] The composite coil is further calendered by a calender to make the layers more tightly bonded and the surface smoother. The calendering pressure is 0.3-0.6MPa.

[0057] 4. Post-processing The composite waterproof membrane is cooled by air or water to reduce its temperature to room temperature.

[0058] The coils are quality inspected, including appearance inspection (whether there are defects such as bubbles, wrinkles, delamination, etc.), thickness measurement (whether it meets the design requirements), and performance testing (such as tensile strength, elongation at break, aging resistance, waterproof performance, etc.).

[0059] According to the test results, the qualified coils are rolled and packaged. When rolling, attention should be paid to the tension control of the coils to avoid loosening or excessive stretching of the coils. The packaging materials can be plastic film or kraft paper to protect the coils from damage during transportation and storage.

[0060] Through the above preparation method, a non-asphalt-based composite waterproofing membrane with good aging resistance, wear resistance and waterproof performance can be obtained. In the actual production process, the process parameters of each link must be strictly controlled to ensure the stability and reliability of product quality. At the same time, the formula and preparation process can be appropriately adjusted and optimized according to the actual production situation and product performance requirements.

[0061] The preparation method of hindered phenol antioxidants is usually carried out in a reactor equipped with a stirrer, a thermometer, and a reflux condenser. The stirrer is used to fully mix the raw materials, the thermometer is used to monitor the reaction temperature, and the reflux condenser can reflux the volatile substances in the reaction process into the reaction system to improve the utilization rate of the raw materials.

[0062] Add p-cresol to the reactor, then slowly add concentrated sulfuric acid as a catalyst, stirring while adding to evenly disperse the catalyst. Afterwards, slowly introduce isobutylene gas under certain temperature and pressure conditions. The reaction temperature is generally controlled at 50-70°C, and the pressure is maintained at 0.2-0.5MPa. Within this temperature and pressure range, the reaction can proceed smoothly, which is conducive to improving the selectivity and yield of the reaction.

[0063] Reaction time and monitoring: The reaction time is usually 4-6 hours. During the reaction, the reaction progress needs to be controlled by observing the phenomena in the reactor (such as color changes, whether bubbles are generated, etc.) and monitoring the reaction temperature and pressure. The content of raw materials and products in the reaction system can be regularly tested by gas chromatography and other analytical methods. When the conversion rate of p-cresol reaches a certain level (such as more than 90%) and the content of BHT no longer increases significantly, the reaction can be considered to be basically completed.

[0064] Post-processing Neutralization and water washing: After the reaction is completed, the reaction mixture must first be neutralized to remove the concentrated sulfuric acid catalyst. Usually, sodium hydroxide solution is used for neutralization to make the pH value of the reaction system reach a neutral pH. After neutralization, water washing is performed to remove water-soluble impurities such as salts generated during the reaction. Water washing generally needs to be repeated several times until the pH value of the water washing liquid remains basically unchanged.

[0065] Separation and purification: The reaction mixture after water washing contains BHT, unreacted raw materials and a small amount of impurities. It is separated and purified by vacuum distillation. Since the boiling point of BHT is relatively high, vacuum distillation can separate BHT from other low-boiling substances at a lower temperature. The fraction collected within a certain temperature and pressure range (determined according to the boiling point of BHT and the vacuum conditions) is the initially purified BHT product.

[0066] Crystallization and drying: In order to further improve the purity of BHT, the initially purified BHT product is crystallized. Generally, BHT is dissolved in an appropriate amount of hot organic solvent (such as ethanol), and then the solution is slowly cooled to allow BHT to crystallize. The crystallized BHT is filtered and finally dried in a vacuum drying oven. The drying temperature is controlled at 50-60°C and the drying time is 4-6 hours to obtain a high-purity 2,6-di-tert-butyl-4-methylphenol finished product.

[0067] The preparation method of phosphate auxiliary antioxidant is that the reaction is usually carried out in a reactor equipped with a stirrer, a thermometer, a reflux condenser and a gas absorption device. The stirrer is used to fully mix the raw materials, the thermometer is used to monitor the reaction temperature, the reflux condenser can reflux the organic solvent in the reaction system to maintain the stability of the reaction system, and the gas absorption device is used to absorb the hydrogen chloride gas generated by the reaction to prevent it from leaking into the environment.

[0068] Addition order and reaction conditions: First, add the solvent (such as toluene) to the reactor, then slowly add 2,4-di-tert-butylphenol and stir to dissolve it. Then, slowly add phosphorus trichloride at low temperature (generally 0-10°C). The temperature must be strictly controlled during the addition process, because phosphorus trichloride reacts violently with water and a large amount of heat is released during the reaction. If the temperature is too high, the reaction may get out of control. After the addition is completed, slowly heat up to the reflux temperature (the reflux temperature of toluene is about 110-112°C) and react for several hours (generally 3-5 hours).

[0069] Post-processing Neutralization and water washing: After the reaction is completed, the reaction system contains hydrogen chloride, which needs to be neutralized. Usually, an alkali solution (such as sodium hydroxide solution) is used for neutralization to make the pH value of the reaction system neutral. After neutralization, water washing is performed to remove salt impurities and unreacted raw materials generated during the reaction. Water washing generally needs to be repeated many times until the pH value of the water washing liquid remains basically unchanged.

[0070] Separation and purification: The reaction mixture after water washing contains antioxidant 168, solvent and a small amount of impurities. It is separated and purified by vacuum distillation. First, the solvent is removed by distillation, and then under vacuum conditions, the product fractions are collected according to the boiling point range of antioxidant 168 (about 180-200°C, the boiling point will decrease under reduced pressure conditions) to obtain preliminarily purified antioxidant 168.

[0071] Crystallization and drying: In order to further improve the purity of antioxidant 168, the initially purified product is subjected to crystallization treatment. Antioxidant 168 is dissolved in an appropriate amount of hot solvent (such as ethanol or methanol), and then the solution is slowly cooled to allow antioxidant 168 to crystallize out. The crystallized antioxidant 168 is filtered and finally dried in a vacuum drying oven. The drying temperature is generally controlled at 50-70°C and the drying time is 4-6 hours to obtain a high-purity tris(2,4-di-tert-butylphenyl) phosphite finished product.

[0072] The method for preparing a nonionic surfactant is to carry out the reaction in a high-pressure reactor, which needs to be equipped with a stirrer, a thermometer, a pressure gauge and a cooling device. The stirrer is used to fully mix the raw materials, the thermometer and the pressure gauge monitor the reaction temperature and pressure respectively, and the cooling device is used to control the temperature during the reaction to prevent the reaction from getting out of control.

[0073] Feeding order and reaction conditions: First, add fatty alcohol and catalyst into the reactor, close the reactor and evacuate to remove air and moisture in the reaction system. Then, slowly introduce ethylene oxide at a certain temperature (generally 120-180°C) and pressure (generally 0.2-0.5MPa). The control of reaction temperature and pressure is very important. Too high temperature may lead to increased side reactions, and too high pressure may pose a safety risk. The introduction rate of ethylene oxide should be moderate to ensure a smooth reaction.

[0074] Reaction time and monitoring: The reaction time depends on the amount of ethylene oxide added and the reaction rate, and generally takes several hours. During the reaction, the reaction progress is judged by monitoring parameters such as pressure, temperature and stirring power in the reactor. When the pressure no longer drops, it indicates that the ethylene oxide has been basically reacted.

[0075] Post-processing Neutralization and water washing: After the reaction is completed, the reaction product must first be neutralized to remove the catalyst. Acid (such as acetic acid) is usually used for neutralization to make the pH value of the reaction system close to neutral. After neutralization, water washing is performed to remove salt impurities and unreacted raw materials generated during the reaction. Water washing generally needs to be repeated several times until the pH value of the water washing liquid remains basically unchanged.

[0076] Separation and purification: The reaction mixture after water washing contains fatty alcohol polyoxyethylene ether, a small amount of impurities and water. The separation and purification is carried out by vacuum distillation. First, water and low-boiling impurities are removed by distillation, and then the product fractions are collected according to the boiling point range of fatty alcohol polyoxyethylene ether under vacuum conditions to obtain preliminarily purified fatty alcohol polyoxyethylene ether.

[0077] Filtration and drying: The preliminarily purified product is filtered to remove possible solid impurities, and then dried in a vacuum drying oven. The drying temperature is generally controlled at 50-70°C and the drying time is 4-6 hours to obtain a high-purity fatty alcohol polyoxyethylene ether finished product.

[0078] The three embodiments of the non-asphalt-based aging-resistant waterproof membrane each have their own characteristics and advantages. Embodiment 1: Although the performance is relatively weak, the cost may be low, and it is suitable for short-term or temporary construction projects and small projects that are cost-sensitive; Embodiment 2: Excellent comprehensive performance, outstanding performance in wear resistance, aging resistance and oxidation resistance, highly reliable, suitable for large public buildings, important infrastructure and construction projects in harsh environments, etc.; Embodiment 3: Balanced performance and cost, at a medium level, can adapt to general use environments, suitable for general commercial buildings and residential projects and medium-sized projects with certain cost requirements. In actual applications, it is necessary to comprehensively consider and select according to the specific situation to achieve a balance between the best waterproof effect and economic benefits.

[0079] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A non-asphalt-based aging-resistant waterproof membrane, characterized in that: The coiled material is composed of a main body layer, a surface anti-aging layer, a bonding layer and a wear-resistant reinforcement layer; The main body layer is composed of thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer and fiber filler; The surface anti-aging layer is composed of nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant; The bonding layer is composed of terpene resin and butyl rubber; The wear-resistant reinforcement layer is composed of methyl methacrylate-butadiene-styrene copolymer, nano-aluminum oxide, gamma-methacryloxypropyltrimethoxysilane, epoxy resin, initiator and accelerator.

2. The non-asphalt-based aging-resistant waterproof membrane according to claim 1, characterized in that: The invention comprises the following components by weight: 40-45 parts by weight of thermoplastic polyolefin resin, 25-30 parts by weight of ethylene-vinyl acetate copolymer, 10-12 parts by weight of fiber filler, 10-15 parts by weight of nano titanium dioxide, 5-10 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 3-5 parts by weight of hindered phenol antioxidant, 2-4 parts by weight of phosphite auxiliary antioxidant, 3-6 parts by weight of organic tin stabilizer, 2-5 parts by weight of rare earth stabilizer. parts, 1-3 parts by weight of silane coupling agent, 1-2 parts by weight of nonionic surfactant, 3-5 parts by weight of terpene resin, 2-4 parts by weight of butyl rubber, 40-50 parts by weight of methyl methacrylate-butadiene-styrene copolymer, 10-16 parts by weight of nano alumina, 3-6 parts by weight of γ-methacryloxypropyltrimethoxysilane, 20-30 parts by weight of epoxy resin, 0.5-1.5 parts by weight of initiator and 0.1-0.4 parts by weight of accelerator.

3. The non-asphalt-based aging-resistant waterproof membrane according to claim 2, characterized in that: The fiber filler is composed of carbon fiber and polyester fiber, the hindered phenol antioxidant is 2,6-di-tert-butyl-4-methylphenol, the phosphate auxiliary antioxidant is triester phosphite, the non-ionic surfactant is fatty alcohol polyoxyethylene ether, the initiator is dibenzoyl peroxide, and the accelerator is dimethylaniline.

4. A method for preparing a non-asphalt-based aging-resistant waterproof coiled material, characterized in that: The following steps are included: Step 1: Purchase and inspect raw materials. Purchase thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer, fiber filler, nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent, non-ionic surfactant, terpene resin, butyl rubber, methyl methacrylate-butadiene-styrene copolymer, nano alumina, γ-methacryloxypropyltrimethoxysilane, epoxy resin, initiator and accelerator according to the formula requirements; Step 2: Preparation of the main body layer: adding thermoplastic polyolefin resin, ethylene-vinyl acetate copolymer and fiber filler into a high-speed mixer, mixing for 15-20 minutes at a temperature of 80-100°C and a rotation speed of 1000-1500r / min, adding the mixed materials into a special extruder for the main body layer, heating and plasticizing in the extruder, extruding through a die to form a main body layer sheet, and then cooling and shaping; Step 3: Preparation of the surface anti-aging layer, adding nano titanium dioxide, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hindered phenol antioxidant, phosphite auxiliary antioxidant, organic tin stabilizer, rare earth stabilizer, silane coupling agent and non-ionic surfactant into another high-speed mixer, mixing at a temperature of 60-80°C for 10-15 minutes, adding the mixed materials into a special extruder for the anti-aging layer, extruding to form an anti-aging layer sheet, and then drying; Step 4: Preparation of the bonding layer: Add the terpene resin and butyl rubber into a small mixer and mix at room temperature for 5-10 minutes; Step 5: Preparation of wear-resistant reinforcement layer: Add nano-alumina to an appropriate amount of ethanol, perform ultrasonic dispersion, slowly drop γ-methacryloxypropyltrimethoxysilane into the above dispersion, stir continuously during the dropwise addition, continue stirring after the dropwise addition is completed, reflux the mixed solution for reaction, and after the reaction is completed, obtain surface-modified nano-alumina by centrifugal separation, wash with ethanol 3-5 times to remove unreacted γ-methacryloxypropyltrimethoxysilane and impurities, and then vacuum dry for use; Prepolymerization reaction: add methyl methacrylate-butadiene-styrene copolymer into a reactor, heat until completely melted, add epoxy resin into the reactor, stir evenly, then add initiator, continue stirring and heating to carry out prepolymerization reaction; Blending reaction: adding the surface-modified nano-alumina to the above-mentioned prepolymer, adding a promoter at the same time, mixing the mixture thoroughly and evenly under high-speed stirring, then heating up to continue the reaction, and after the reaction is completed, naturally cooling to room temperature to obtain a wear-resistant reinforcement layer; Adding the prepared wear-resistant reinforcement layer into a special extruder for the wear-resistant reinforcement layer, and extruding to form a wear-resistant reinforcement layer sheet; Step 6: Compounding the coiled material: Compounding the prepared main layer, surface anti-aging layer, bonding layer and wear-resistant reinforcement layer through a laminating device in the order of main layer-bonding layer-wear-resistant reinforcement layer-bonding layer-surface anti-aging layer, and further calendering the compounded coiled material through a calendering machine; Step seven: Post-processing, cooling the composite waterproof membrane.

5. The method for preparing a non-asphalt-based aging-resistant waterproof coiled material according to claim 4, characterized in that: The ultrasonic dispersion time in step 5 is 30-60 minutes, and the stirring time after the dropwise addition is set to 2-3 hours; The reflux reaction temperature of the mixed solution is set to 60-80°C, and the reflux reaction time is set to 4-6 hours; The vacuum drying temperature is set to 80-100°C, and the vacuum drying time is set to 6-8 hours.

6. The method for preparing a non-asphalt-based aging-resistant waterproofing membrane according to claim 4, characterized in that: In the prepolymerization reaction, the heating temperature is set to 80-100° C., the heating temperature is set to 120-130° C., and the prepolymerization reaction time is set to 1-2 hours.

7. The method for preparing a non-asphalt-based aging-resistant waterproofing coiled material according to claim 4, characterized in that: The heating temperature in the blending reaction is set to 140-150° C., and the reaction time is set to 2-3 hours.

8. The method for preparing a non-asphalt-based aging-resistant waterproof coiled material according to claim 2, characterized in that: The preparation method of 2,6-di-tert-butyl-4-methylphenol comprises the following steps: adding p-cresol into a reaction kettle, then slowly adding concentrated sulfuric acid as a catalyst, stirring while adding to uniformly disperse the catalyst, then slowly introducing isobutylene gas under certain temperature and pressure conditions, the reaction temperature is generally controlled at 50-70°C, the pressure is maintained at 0.2-0.5MPa, the reaction time is 4-6 hours, after the reaction is completed, neutralizing with sodium hydroxide solution to make the pH value of the reaction system reach neutrality, after neutralization, washing with water to remove water-soluble impurities such as salts generated during the reaction, the washing with water generally needs to be repeated multiple times until the pH value of the washing liquid remains substantially unchanged, and separating and purifying with a reduced pressure distillation method to obtain 2,6-di-tert-butyl-4-methylphenol.

9. The method for preparing a non-asphalt-based aging-resistant waterproofing membrane according to claim 2, characterized in that: The preparation method of the triester phosphite comprises the following steps: adding solvent toluene into a reaction kettle, then slowly adding 2,4-di-tert-butylphenol, stirring to dissolve it, then slowly dropping phosphorus trichloride at a low temperature of 0-10°C, strictly controlling the temperature during the dropping process, slowly heating to a reflux temperature of about 110-112°C after the dropping is completed, reacting for 3-5 hours, neutralizing and washing with water after the reaction, and then separating and purifying by a reduced pressure distillation method to obtain the triester phosphite.

10. The method for preparing a non-asphalt-based aging-resistant waterproofing membrane according to claim 2, characterized in that: The preparation method of the fatty alcohol polyoxyethylene ether comprises the following steps: adding fatty alcohol and an alkali catalyst into a reaction kettle, closing the reaction kettle and evacuating the reaction kettle to remove air and moisture in the reaction system, then slowly introducing ethylene oxide at a temperature of 120-180° C. and a pressure of 0.2-0.5 MPa to react, neutralizing and washing after the reaction, and then separating and purifying by a reduced pressure distillation method to obtain the fatty alcohol polyoxyethylene ether.

Citation Information

Patent Citations

  • Macromolecular waterproof coiled material and special equipment and manufacturing method thereof

    CN105856581A

  • Method for preparing waterborne epoxy acrylate coating

    CN107880741A

  • Magnetic polymer waterproof coiled material

    CN115162539A

  • Negative oxygen ion epoxy coiled material and preparation method thereof

    CN116751500A

  • Large-diameter polyethylene pipe

    CN208871173U